COMPOSITE PARABOLIC COLECTOR FOR SOLAR THERMA - Pacheco Luján, Werner (2006)
The Composed Parabolic Collector (CPC) is made up of two parabolic surfaces whose center is the same. In such a center, a black-painted copper tube is placed to transform the sunlight that comes to the copper surface heating it; the CPC concentrates the light in the center, and it can even receive rays with oblique incidence according to its angle of acceptance, the one that could be increased with copper fins welded to the copper tubes. This set also allows to receive and to concentrate diffuse light in a cloudy day. Four Collectors of 1.00 m x 1.25 m are connected to an electrical therma of 500 liters, that will store the water warmed up by the collectors, and through the thermosiphon effect, this one has also has electrical resistance in case there were several non-sunny days.